MEDICAL AND SOCIAL PROBLEM OF HEMATOLOGIC DISEASES OF UKRAINIAN POPULATION - Popadynets, O.G. (World of Medicine and Biology, 2017)
The central organ of hemopoiesis and immune protection is a red bone marrow that contains not only hemopoietic stem cells, but also it forms a unique microenvironment for their proliferation and differentiation. It is a red bone marrow that regulates access to peripheral blood of mature blood corpuscle. Pathological deviations in the blood system are considered to be an increase or decrease in the quantitative composition of individual cells, as well as changes in their ratios relative to each other, or changes in their form.